Optimizing road traffic of emergency vehicles - Hasnaa Elmandili; Hamza Toulni; Benayad Nsiri (2013 International Conference on Advanced Logistics and Transport, 2013)
In our application, and in the context of optimizing the flow of an emergency vehicle in time, we will rely on two tools (mathematics and computer science) in order to avoid delays and risks that characterize the movement of these vehicles. We will use VANET networks as a transmission system to retrieve information about the road incident, and after that, we shall use the Kalman algorithm for tracking our vehicle clarify to specify its position on the predefined path in order to intervene and change its direction towards a safer driving at the same point.
Keywords: VANET; Kalman; SUMO